Sea Power and American Interests in the Western Pacific - Gompert, David C. (RAND Corporation, 2013)
This book examines the strategic choices that American and Chinese decisionmakers face regarding sea power in the Western Pacific, shaped by geography, history, technology, and politics. In particular, the author explores the potential for cooperation on maritime security in the Western Pacific, and how the United States might pursue such cooperation as part of a broader strategy to advance its interests in the region.